A Unique Genetically Encoded FRET Pair in Mammalian Cells. (9th February 2017) - Mitchell, Amanda L.; Addy, Partha Sarathi; Chin, Melissa A.; Chatterjee, Abhishek
Abstract: Förster resonance energy transfer (FRET) between two suitable fluorophores is a powerful tool to monitor dynamic changes in protein structure in vitro and in vivo. The ability to genetically encode a FRET pair represents a convenient "labeling‐free" strategy to incorporate them into target protein(s). Currently, the only genetically encoded FRET pairs available for use in mammalian cells use fluorescent proteins. However, their large size can lead to unfavorable perturbations, particularly when two are used at the same time. Additionally, fluorescent proteins are largely restricted to a terminal attachment to the target, which might not be optimal. Here, we report the development of an alternative genetically encoded FRET pair in mammalian cells that circumvents these challenges by taking advantage of a small genetically encoded fluorescent unnatural amino acid as the donor and enhanced green fluorescent protein (EGFP) as the acceptor. The small size of Anap relative to fluorescent proteins, and the ability to co‐translationally incorporate it into internal sites on the target protein, endows this novel FRET pair with improved versatility over its counterparts that rely upon two fluorescent proteins. Abstract : Time for Anap : A genetically encoded FRET pair was developed in mammalian cells that uses a small fluorescent unnatural amino acid, Anap, as the donor and EGFP as the acceptor. Unlike genetically encoded FRET pairs consisting of two fluorescent proteins, the use of Anap enables facile internal labeling and minimizes the risk of target perturbation.